Matrix‐assisted laser desorption/ionization mass spectrometry imaging: a powerful tool for probing the molecular topology of plant cutin polymer. (4th November 2014) - Veličković, Dušan; Herdier, Hélène; Philippe, Glenn; Marion, Didier; Rogniaux, Hélène; Bakan, Bénédicte
Summary The cutin polymers of different fruit cuticles (tomato, apple, nectarine) were examined using matrix‐assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) after in situ release of the lipid monomers by alkaline hydrolysis. The mass spectra were acquired from each coordinate with a lateral spatial resolution of approximately 100 μm. Specific monomers were released at their original location in the tissue, suggesting that post‐hydrolysis diffusion can be neglected. Relative quantification of the species was achieved by introducing an internal standard, and the collection of data was subjected to non‐supervised and supervised statistical treatments. The molecular images obtained showed a specific distribution of ions that could unambiguously be ascribed to cutinized and suberized regions observed at the surface of fruit cuticles, thus demonstrating that the method is able to probe some structural changes that affect hydrophobic cuticle polymers. Subsequent chemical assignment of the differentiating ions was performed, and all of these ions could be matched to cutin and suberin molecular markers. Therefore, this MALDI‐MSI procedure provides a powerful tool for probing the surface heterogeneity of plant lipid polymers. This method should facilitate rapid investigation of the relationships between cuticle phenotypes and the structure of cutin within a large population of mutants.